Sosialisasi Minuman Herbal Daun Senduduk (Melastoma malabathricum L.) Bernilai Jual Di Kampung Benteng Hulu - Setyawatiningsih, Sri Catur; Cinta Namira; Dhira Hilwatul Jannah; Sadini Aprilia; Natasya Aprilia Wati; Wan Fithratunnazhifah; Tania Tarbin; Desi Sri Wahyuni; Janetty Lumban Batu; Lathifa Desra Tami; Rifki Fawwaz Khairi; Ahmad Dhani Fiandri (LPPM UMRI, 2026)
The senduduk plant (Melastoma malabathricum L.) is abundant in Benteng Hulu Village, yet it has not been utilized or recognized for its economic value. This community service initiative aims to improve the community's ability to process senduduk leaves into valuable herbal beverages. Methods employed included outreach and processing training, including sorting, washing, drying, grinding, and packaging. Evaluation was conducted through organoleptic testing and interviews. Ginger (Zingiber officinale) was added to the herbal beverage during production to reduce the astringent taste caused by tannins and enhance the beverage's flavor and functional value. Interview results indicate an increase in community knowledge regarding the processing of senduduk leaves into value-added herbal beverages. The herbal beverages were generally well-received for their pleasant taste and aroma (76,67%). Most respondents (66,67%) reported feeling immediate benefits after consuming the beverage. Twenty-three percent rated the experience as average, and the remainder stated they did not feel any effects. Approximately 80% of respondents reported a reduction in astringency. Additionally, all respondents expressed interest in the product, indicating its potential for development as a household-scale business based on local resources.